2022
DOI: 10.3233/wor-205196
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of schoolteachers towards students with epilepsy in Al-Jouf, Saudi Arabia

Abstract: BACKGROUND: Epilepsy is a common disorder in which brain activity becomes abnormal that causes recurrent seizures or periods of jerky movement of the whole body. Immediately after a seizure, people are often transiently confused, weak and unable to communicate. OBJECTIVE: This study assesses the knowledge, attitude, and practice (KAP) of school teachers towards an epileptic child. METHODS: This cross-sectional study was conducted among primary and secondary school teachers from different schools in Sakaka, Dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Teachers would do the following to a seizing child: 52% would pull the child's tongue out, 21.6% would put a spoon in the child's mouth, 14.1% would remove any tight clothing, and 79.7% would take the child to the hospital. The study concluded that the majority of Aljouf schoolteachers had adequate knowledge about students with epilepsy, but they needed more information about how to practice with students with epilepsy [14].…”
Section: Interpretation Of the Main Study Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers would do the following to a seizing child: 52% would pull the child's tongue out, 21.6% would put a spoon in the child's mouth, 14.1% would remove any tight clothing, and 79.7% would take the child to the hospital. The study concluded that the majority of Aljouf schoolteachers had adequate knowledge about students with epilepsy, but they needed more information about how to practice with students with epilepsy [14].…”
Section: Interpretation Of the Main Study Findingsmentioning
confidence: 99%
“…These attitudes shape their actions and reactions to challenges, incentives, and rewards [13]. While attitude is a complicated and ethereal concept, recent research has shown how teachers' attitudes can influence their actions, which can have negative effects on children who have epilepsy [14][15][16].…”
Section: Introductionmentioning
confidence: 99%